1984
DOI: 10.1111/1523-1747.ep12261472
|View full text |Cite
|
Sign up to set email alerts
|

Histologic Changes in the Skin of the Rhino Mouse (hrrhhrrh) Induced by Retinoids

Abstract: The effects of four retinoids, all-trans-retinoic acid (RA), 13-cis-retinoic acid (13-cis-RA), aromatic retinoid, and arotinoid ethyl ester ( arotinoid ) were examined on the skin of the rhino mouse. Rhino mouse skin is characterized by the presence of keratin-containing utricles attached to the epidermis, and subcutaneous cysts, both of which are derived from hair follicles. The utricles were examined in horizontal sheets of epidermis, and in vertical histologic sections. After applications of 0.1 ml of 0.1% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
20
1

Year Published

1988
1988
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(29 citation statements)
references
References 6 publications
8
20
1
Order By: Relevance
“…On all the parameters studied, RAL had the same activity as RA; further studies on dose-dependent activity would be interesting to perform. These effects are those of retinoids, due to an induction of epidermal cell proliferation which is specific to retinoid treatment and well known in the rhino mouse model [5]. …”
Section: Discussionmentioning
confidence: 99%
“…On all the parameters studied, RAL had the same activity as RA; further studies on dose-dependent activity would be interesting to perform. These effects are those of retinoids, due to an induction of epidermal cell proliferation which is specific to retinoid treatment and well known in the rhino mouse model [5]. …”
Section: Discussionmentioning
confidence: 99%
“…The rhino mouse has been used as an animal model in experiments of keratolytic agents such as retinoids, because of the similarity of its horn-filled utriculi to comedones [3,5] . Retinoids are known to induce comedolysis and epidermal thickening.…”
Section: Discussionmentioning
confidence: 99%
“…Mezick et al [4] reported a method of examining sheets of rhino mouse skin in a horizontal approach. Ashton et al [5] used this method for measuring the diameter of utriculi. The results showed that utricular count is different if the horizontal or the vertical approach is used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations